2012
DOI: 10.1029/2012je004064
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory experiments on crater scaling‐law for sedimentary rocks in the strength regime

Abstract: [1] We systematically conducted impact cratering experiments with sedimentary rocks at 0.8-7.1 km/s using various projectiles with 1.1-15 g/cm 3 in density. The crater diameter, depth, and volume are investigated and compared with the results for igneous rocks. Then, using the non-dimensional parameters, the normalized crater diameter p D , the normalized depth p d , the normalized volume p V , the target strength per specific energy p 3 , and the target and projectile density ratio p 4 , the scaling laws,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…Laboratory high-velocity impact experiments, using millimeter-to-centimeter size projectiles to study cratering in the strength regime, were performed for various targets with porosities ranging from 0% to more than 90%. The morphology and dimensions, i.e., diameter and depth, were studied for weak cemented basalt targets (Housen, 1992), sandperlite-fly ash mixture targets (Housen and Holsapple, 2003), sintered glass bead targets (Love et al, 1993;Michikami et al, 2007;Hiraoka et al, 2008;Okamoto et al, 2015; Okamoto and Nakamura 2017), cement mortar targets (Michikami et al, 2017), gypsum targets Okamoto and Nakamura, 2017), and natural porous rocks (Baldwin, et al, 2007;Kenkmann, et al, 2011;Suzuki et al, 2012;Poelchau, M. H., 2014;Flynn, et al, 2015;Okamoto and Nakamura, 2017). Table 1 summarizes the target density, porosity, strength, impact velocity, and projectile material and diameter of these experiments.…”
Section: Targets In the Strength Regimementioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory high-velocity impact experiments, using millimeter-to-centimeter size projectiles to study cratering in the strength regime, were performed for various targets with porosities ranging from 0% to more than 90%. The morphology and dimensions, i.e., diameter and depth, were studied for weak cemented basalt targets (Housen, 1992), sandperlite-fly ash mixture targets (Housen and Holsapple, 2003), sintered glass bead targets (Love et al, 1993;Michikami et al, 2007;Hiraoka et al, 2008;Okamoto et al, 2015; Okamoto and Nakamura 2017), cement mortar targets (Michikami et al, 2017), gypsum targets Okamoto and Nakamura, 2017), and natural porous rocks (Baldwin, et al, 2007;Kenkmann, et al, 2011;Suzuki et al, 2012;Poelchau, M. H., 2014;Flynn, et al, 2015;Okamoto and Nakamura, 2017). Table 1 summarizes the target density, porosity, strength, impact velocity, and projectile material and diameter of these experiments.…”
Section: Targets In the Strength Regimementioning
confidence: 99%
“…The former had strength four times the strength of the latter. Baldwin et al (2007), Suzuki et al (2012), and Poelchau et al (2014) compiled results of porous rock targets using conventional cratering scaling laws (Holsapple and Schmidt, 1982) and showed that the cratering efficiency, defined by the ratio of excavated mass to projectile mass, for the porous targets was less than that of competent rocks for the same impact conditions defined by a nondimensional parameter involving the mechanical strength of the target, such as .…”
Section: Cratering Efficiencymentioning
confidence: 99%
“…The final problem is the constant-Y assumption, which is only valid for metal-like targets. Despite this limitation, the constant-Y assumption has been widely used to derive the π-group scaling laws (e.g., Gault, 1973, Suzuki et al, 2012. Thus, we decided to present the cratering processes in the strength-dominated regime based on the constant-Y assumption.…”
Section: Energies In Stream Tubesmentioning
confidence: 99%
“…It should be mentioned that, in principle, dimensional analysis does not provide absolute values, including the position-dependent ejection velocity and the transient crater radius. Thus, the scaling parameters, including K 1 , µ, and ν, have been widely explored empirically based on both laboratory and numerical experiments (e.g., Gault, 1973, Gault and Wedekind, 1977, Schmidt, 1980, Schmidt and Housen, 1987, O'Keefe and Ahrens, 1993, Cintala et al, 1999, Wünnemann et al, 2006, 2016, Yamamoto et al, 2006, Baldwin et al, 2007, Elbeshausen et al, 2009, Kraus et al, 2011, Kenkmann et al, 2011, Suzuki et al, 2012, Güldemeister, 2015, Prieur et al, 2017. However, existing data pertaining to crater radii have not converged to the single universal line predicted by Eq.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Fujiwara et al (1993Fujiwara et al ( , 2014 produced distinctive impact craters on mainly cylindrical targets with a wide range of radii in a laboratory and presented the empirical relations between crater diameter, depth, mass, and target curvature. Walker et al (2013) had an aluminum sphere impact into granite spheres of 1-m diameter at 2 km/s in order to examine the scale size effect of momentum enhancement in the momentum transfer in impacts.…”
Section: Introductionmentioning
confidence: 99%